Inclusive approaches to strategic personnel motivation in the context of corporate social responsibility - Дуднєва, Юлія Ернстівна; Соболєв, Тимур Едуардович; Dudnieva, I. E.; Soboliev, T. E. (Харків : ФОП Лібуркіна Л. М., 2025)
The article explores inclusive approaches to strategic personnel motivation in the context of corporate social responsibility (CSR), highlighting the importance of human capital management under conditions of social and economic transformation. The study emphasizes that personnel motivation today extends beyond traditional economic incentives and increasingly relies on inclusive mechanisms that ensure fairness, equal access to opportunities, and the recognition of diversity within organizations. The authors argue that strategic motivation policies must be integrated with CSR objectives, as this alignment not only improves employee satisfaction and loyalty but also strengthens corporate reputation and long-term competitiveness. A conceptual framework is proposed for understanding how inclusive motivation practices, such as flexible reward systems, participatory decision-making, professional development opportunities, and social support measures, can become drivers of sustainable organizational growth. Special attention is paid to the Ukrainian context, where war-related challenges and the processes of European integration create new requirements for HR policy and the adoption of international CSR standards. The analysis demonstrates that inclusive motivational strategies can reduce the negative effects of uncertainty, support employee resilience, and promote trust within organizations. The article draws on comparative analysis of international practices and domestic trends, offering recommendations for Ukrainian companies to balance economic performance with social responsibility through personnel management. The results contribute to the development of modern management theory by linking inclusive HR strategies with CSR and provide practical tools for managers aiming to foster resilience, adaptability, and ethical corporate culture. These findings may also serve as a basis for future research on the transformation of motivation systems in emerging economies and their role in achieving sustainable development goals.

У статті досліджено інклюзивні підходи до стратегічної мотивації персоналу в контексті корпоративної соціальної відповідальності (КСВ), що набуває особливого значення в умовах соціально-економічних трансформацій. Наголошено, що сучасна мотивація працівників виходить за межі традиційних економічних стимулів і дедалі частіше спирається на інклюзивні механізми, які забезпечують справедливість, рівний доступ до можливостей та визнання різноманіття в організаціях. Аргументовано, що стратегічна політика мотивації персоналу повинна бути інтегрована з цілями КСВ, оскільки таке поєднання не лише підвищує задоволеність і лояльність працівників, а й зміцнює репутацію компанії та її довгострокову конкурентоспроможність. Запропоновано концептуальні підходи до розуміння того, як інклюзивні практики мотивації, а саме гнучкі системи винагород, участь у прийнятті рішень, можливості професійного розвитку та соціальні програми підтримки, можуть стати драйверами сталого організаційного розвитку. Особливу увагу приділено українському контексту, коли воєнні виклики та процеси євроінтеграції формують нові вимоги до кадрової політики та впровадження міжнародних стандартів КСВ. Показано, що інклюзивні мотиваційні стратегії здатні зменшувати негативний вплив невизначеності, підтримувати стійкість персоналу та формувати довіру в організаціях. На основі порівняльного аналізу міжнародних практик і вітчизняних тенденцій сформульовано рекомендації для українських компаній щодо поєднання економічної результативності з соціальною відповідальністю у сфері управління персоналом. Отримані результати розвивають сучасну теорію менеджменту, поєднуючи інклюзивні HR-стратегії з КСВ, та пропонують практичні інструменти для керівників, які прагнуть підвищити адаптивність, стійкість і етичність корпоративної культури. Висновки роботи можуть стати підґрунтям для подальших досліджень трансформації систем мотивації в економіках, що розвиваються, та їхнього внеску у досягнення цілей сталого розвитку.
Інклюзивні підходи до стратегічної мотивації персоналу в контексті корпоративної соціальної відповідальності
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; strategic personnel motivation; інклюзивні практики управління; inclusive HR practices; інклюзивні практики управління; corporate social responsibility; корпоративна соціальна відповідальність; HR-management; HR-менеджмент; sustainable development; сталий розвиток